Workplace Bullying, Turnover Intention, and the Moderating Role of Kinship Employee Engagement - Eka Pariyanti; Isman; Delila Fitri Harahab (International Journal of Management, Economic, Business and Accounting, 2023)
Purpose of the study — Testing the Relationship between Workplace Bullying and Turnover Intention, and Examining Kinship Employee Engagement as a Moderating Variable in that Relationship Research method— This Study Conducted in Lampung, Indonesia, Involving Private University Lecturers as Respondents. Data Analysis Utilized JASP. Result— The Results of this Study Indicate a Positive Relationship between Workplace Bullying and Turnover Intention. Kinship Employee Engagement is Found to Moderate this Relationship. Conclusion— All Hypotheses are Supported, Signifying the Importance for Institutions to Strengthen Kinship Employee Engagement.